Ureteral reconstruction is safe and successful in poorly functioning kidneys - Grimaud, Logan W.; Sury, Kiran; Salvino, Matthew; Livingston, Austin; Lentz, Aaron C.; Peterson, Andrew C. (Frontiers in Urology, 2025)
ObjectivesPatients with a poorly functioning kidney, defined as less than 20% differential renal function, have historically been considered poor candidates for ipsilateral ureteral reconstruction for stricture. To determine if renal function can be safely preserved in poorly functioning kidneys with ureteral stricture, we evaluated patient outcomes following ureteral reconstruction.MethodsWe conducted a review of 114 adult patients who underwent ureteral reconstructive surgery at our institution between 2013 and 2023. Patients with poorly functioning ipsilateral kidneys were identified by a preoperative renal scan (MAG3 renogram). Variables of interest included patient characteristics, peri/postoperative outcomes, resolution of hydronephrosis, pre/postoperative renal function, and preservation of renal parenchyma.ResultsOf the 8 patients meeting inclusion criteria, 5 underwent bladder elongation psoas hitch (BEPH), 1 ileal ureter, 1 ileal ureter with BEPH, and 1 ureteroureterostomy. Median preoperative differential renal function was 16.0% with a median preoperative serum creatinine (sCr) of 1.70 mg/dL before decompression and 1.35mg/dL after percutaneous nephrostomy tube (PCN) placement. Preoperative median average renal parenchyma thickness (RPT) was 14.5mm. At 6-month follow-up, median sCr and RPT were preserved at 1.25mg/dL (p= 0.084) and 14.3 mm (p=0.41), respectively. At median follow-up of 49.2 months, all patients had a successful repair, defined as no reinsertion of stent/PCN, resolution of hydronephrosis, and no return to the operating room for revision or nephrectomy. Median sCr at last follow-up showed sustained improvement at 1.22 (p=0.0097).ConclusionsReconstruction can be successful for obstructed kidneys with less than 20% differential function and may be considered prior to nephrectomy.